Expeditious ‘On-Water’ Cycloaddition between N-Substituted Maleimides and Furans - Gil, María Victoria; Luque-Agudo, Verónica; Román, Emilio; Serrano, José Antonio (Synlett, 2014)
Cycloaddition reactions between N-alkyl and N-aryl-substituted maleimides and furan derivatives have been carried out using the ‘on-water’ methodology. Transformations are faster and products can easily be isolated by simple workup protocols, often in quantitative yields.
Keywords: cycloaddition; heterocycles; green chemistry